Multi-point die electromagnetic incremental forming for large-sized sheet metals. (February 2021) - Feng, Fei; Li, Jianjun; Chen, Rongchuang; Huang, Liang; Su, Hongliang; Fan, Suo
Abstract: Multi-point die electromagnetic incremental forming is a novel forming method, which is aimed at large-sized sheet metal forming combining electromagnetic incremental forming with multi-point die. The multi-point die can form different curved surfaces without replacing the die; as a result, multi-point die electromagnetic incremental forming can form large-sized workpieces with different curved shapes. A finite element model of multi-point die electromagnetic incremental forming is established. The deformation process of large-sized workpieces is discussed during the first discharge of coil. The influence of multistep forming on the forming quality of sheet metals is explained. Simulation results are basically consistent with the experimental ones. The feasibility of this technology is verified through the experiment of multi-point electromagnetic incremental forming.